2022
DOI: 10.1021/acs.macromol.2c00651
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Polystyrene via the Cleavable Comonomer Approach

Abstract: Polystyrene (PS) is a major commodity polymer widely used in various applications ranging from packaging to insulation thanks to its low cost, high stiffness, and transparency as well as its relatively high softening temperature. Similarly to all polymers prepared by radical polymerization, PS is constituted of a C–C backbone and thus is not degradable. To confer degradability to such materials, the copolymerization of vinyl monomers with a cyclic monomer that could undergo radical ring-opening is an efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 53 publications
4
67
0
Order By: Relevance
“…While it has been shown that DOT does not easily copolymerize with S in anisole at 80 °C, ,, its free-radical aqueous emulsion copolymerization at the same temperature showed a more homogeneous distribution of DOT units in the PS backbone due to a compartmentalization effect and/or the absence of solvent . Our results also confirm the strong effect of increasing temperature, which tends to drastically promote DOT incorporation, as recently shown during its free-radical copolymerization with S in anisole at 150 °C . In addition, the expected difference in water solubility between DOT and S may also result in a higher concentration of DOT in the growing particles and, thus, a faster consumption.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…While it has been shown that DOT does not easily copolymerize with S in anisole at 80 °C, ,, its free-radical aqueous emulsion copolymerization at the same temperature showed a more homogeneous distribution of DOT units in the PS backbone due to a compartmentalization effect and/or the absence of solvent . Our results also confirm the strong effect of increasing temperature, which tends to drastically promote DOT incorporation, as recently shown during its free-radical copolymerization with S in anisole at 150 °C . In addition, the expected difference in water solubility between DOT and S may also result in a higher concentration of DOT in the growing particles and, thus, a faster consumption.…”
Section: Resultssupporting
confidence: 86%
“…Like A1 , the faster incorporation of DOT during the copolymerization led to a decrease in F DOT with S conversion from 5.3 to 1.3 mol % (Figure a). While it has been shown that DOT does not easily copolymerize with S in anisole at 80 °C, ,, its free-radical aqueous emulsion copolymerization at the same temperature showed a more homogeneous distribution of DOT units in the PS backbone due to a compartmentalization effect and/or the absence of solvent . Our results also confirm the strong effect of increasing temperature, which tends to drastically promote DOT incorporation, as recently shown during its free-radical copolymerization with S in anisole at 150 °C .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Despite the ability to make degradable copolymers with narrow size distributions, the seemingly unpreventable loss of typically 50% of the DOT feed and the inability to form polymers from formulations containing more than 15 mol % of DOT meant that it was not possible to make copolymers containing more than ∼7 mol % DOT through the above methods. Although copolymers with lower DOT content have been shown to be useful (e.g.,, fully degradable networks), ,, we sought to increase the DOT content of ATRP-made copolymers. In a typical copolymerization, approximately 25 μmol of DOT were converted to lactone.…”
Section: Resultsmentioning
confidence: 99%